Doing things differently: Rethinking monitoring and evaluation to unde rstand change - Saferworld (Saferworld, 2016)
Doing things differently: Rethinking monitoring and evaluation to unde rstand change Learning paper Over the past four years, Saferworld has put in place a way of monitoring, evaluating and learning from our wor k focused on behaviour and relationship change. This paper outlines th e process we have gone through to adapt, embed, and embrace an approac h inspired by Outcome Mapping and Outcome Harvesting (OH). Key benefit s of our monitoring, evaluation and learning approach are: It is simpl e, but promotes complex discussion and analysis. It allows conflict- a nd gender-sensitivity to be built into programmes; it promotes analysi s of and adaptation to context. Bringing front-line staff and partners into wider conversations with others substantially increases cross-or ganisational learning.